Analysis and comparison of the trends in the burden of migraine in China and globally from 1990 to 2021, with a forecast to 2031 - Tang, Wenjun; Tang, Liyan; Li, Aiguo; Zhang, Wei; Qin, Chaosheng; Chen, Lixue (Frontiers in Neurology, 2025)
BackgroundMigraine is a prevalent neurological disorder in China and globally, imposing significant burdens on individuals and societies. The goal of this study was to characterize age- and sex-specific temporal patterns in migraine burden in China and worldwide from 1990 to 2021, focusing on incidence, prevalence, and disability-adjusted life years (DALYs).MethodsThis retrospective population-based study utilized data from the Global Burden of Disease (GBD) Study in 2021 to analyze the characteristics of migraine burden in China and globally. The study focused on changes in incidence, prevalence, and DALYs. Joinpoint analysis was employed to calculate the average annual percentage change (AAPC) and the corresponding 95% confidence interval (95% CI) to assess trends in the burden of migraine. The Autoregressive Integrated Moving Average (ARIMA) model was utilized to predict the migraine burden for the next decade.ResultsThe worldwide age-standardized incidence rate (ASIR) of migraine rose from 1136.90/100,000 to 1153.20/100,000 between 1990 and 2021, whereas the ASIR in China grew from 917.35/100,000 to 975.61/100,000. Globally, the age-standardized prevalence rate (ASPR) rose from 14027.65/100,000 to 14246.55/100,000, while in China, it rose from 10948.52/100,000 to 11777.51/100,000. Female rates consistently exceed male rates across all age groups. Migraine incidence peaked in the 10–14 age group, while the prevalence and disability-adjusted life years (DALYs) peaked in the 30–34 age group for both females and males in 2021. The ARIMA model forecasts an upward trend in the ASIR and age-standardized DALYs rate (ASDR) for males in China over the next decade. Furthermore, the ASIR, ASDR, and ASPR for males globally, along with the ASIR and ASPR for females globally, are also anticipated to increase by 2031.ConclusionOur findings indicate a rising burden of migraine in China and globally. Females are more susceptible to migraine in all age groups. The burden of migraine is age-related, with adolescents and youths facing a higher risk. More research is needed to determine the risk factors and illness patterns linked to migraine to facilitate early diagnosis, prompt therapies, and lessen patient burden, especially for females and adolescents.